Evaluation of Post–vaccination Symptoms of COVID 19 Vaccines among People in Basrah- Iraq Society - Aseel k. Thamer (Institute of Medico-legal Publications Pvt Ltd, 2022)
Introduction: Vaccines are one of the most effective interventions for destroying COVID-19. Many organizationshave worked to establish an efficient and safe preparation in the minimum time possible. Currently, severalproducts that different in form and effectiveness are approved for sale.Objectives: The goal of this study was to obtain evidence on COVID-19 vaccination adverse effects.Methodology: A cross-sectional study was made between October and December 2021 to obtain data on theinfluence of the COVID-19 vaccine among people in the Iraq- Basrah. There were two types of questions listed.The first one covers the subject’s background information, such as nationality, gender, age, educational level, andpast COVID 19 infection. The second set of questions focused on information about the COVID-19 vaccines andtheir side effects.Result: Local site adverse reaction, Hypersensitivity reaction, bone and muscle pain, headache and fever weremore common in persons received second dose than in participant received first dose. There was a significantdifference in the number of people those under 60 years of age who reported fever, headache, bone and musclepain compared to those 60 years old and over.conclusion: The COVID-19 vaccine’s side effects are similar to those seen with earlier immunizations, and themost of them are tolerable.